2009 American Control Conference 2009
DOI: 10.1109/acc.2009.5159831
|View full text |Cite
|
Sign up to set email alerts
|

Information broadcasting algorithm for Finite-Time Reaching-at-Risk Consensus with application to weapon-target assignment

Abstract: We propose a randomized algorithm aimed at reaching, in finite time, exact consensus among a set of agents that are linked though a connected, possibly time-varying, graph. The information exchanged among neighboring agents is limited in size, by randomly selecting the content from an agent internal state. The time needed to reach the agreement is a random variable, whose empirical cumulative distribution function is utilized to determine a stopping rule that ensures consensus is achieved with a prescribed con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…A detailed presentation of the high-level DM is available in reference [1], where it is shown that a parallel version of the cross-entropy method can solve moderately complex multirouting-type, multiformation-target assignment problems with relatively short processing times. To compute new lists of targets whenever the evolution of the operation theatre is deemed significant enough, the algorithm is distributed among the formations, which share information through a communication network [2]. From Fig.…”
Section: Hierarchical Decision Makingmentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed presentation of the high-level DM is available in reference [1], where it is shown that a parallel version of the cross-entropy method can solve moderately complex multirouting-type, multiformation-target assignment problems with relatively short processing times. To compute new lists of targets whenever the evolution of the operation theatre is deemed significant enough, the algorithm is distributed among the formations, which share information through a communication network [2]. From Fig.…”
Section: Hierarchical Decision Makingmentioning
confidence: 99%
“…There are exactly n 2 q distinct utility matrices U r that are in the set S 2 3 . It comes from the fact that entries of U r ∈ L u over [τ o , τ o+1 ) must satisfy a i,ko = a i,lo and a j,lo = a j,ko .…”
Section: Proofmentioning
confidence: 99%
“…However, the described method requires the graph to be fully connected for at least one time-step. A data aggregation based algorithm was proposed in [8]. Such an approach requires additional memory compared to linear iterations strategies.…”
Section: Introductionmentioning
confidence: 99%
“…However, the described method requires the graph to be fully connected for at least one time-step. A data aggregation based algorithm was proposed in [3]. Such an approach requires additional memory compared to linear iterations strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Algorithms that enable such consensus reaching belong typically to two classes: Distributed averaging based algorithms and probabilistic counting approaches, such as randomized gossip schemes [3].…”
Section: Introductionmentioning
confidence: 99%